Art as a posthuman environment: the ecology of Dao - D'Ambrosio, Francesco (Scenari, 2021)
nstrous as the context in which it lives in, and also an always active laboratory of civil society. From a ecology point of view it can be seen as the place, as well as the privileged habitat, of collective memory through which to define cultures, identities and social affiliations. From the sociological point of view, art is not just collection and / or reproduction of objects, but a set of acts of consumption and signification that enrich the works of many and (sometimes) unexpected meanings. These processes of “meaning negotiation” are set to de- and re-structure themselves with the new digital subjectivities posed as remediated forms of human becoming, beyond the machinic cyborg (R. Braidotti 2014). What turns out to be important within the artistic experiences is the role of the spectator who, far from being an only contemplating subject, lives the art through very particular critical journeys. Through this approach and under the influence of the oriental philosophy of the Dao, and therefore the idea of ​​cosmos that makes the chimeric hybrid a speakable and natural being, new horizons of meaning and new conceptions of the human are discovered. In this work art is proposed as a medial environment to satisfy the needs of an equally complex medium, that is mankind in his body and consciousness traits. Therefore, we are dealing with a new posthuman subjectivity that is not built within the boundaries of flash or within the boundaries advocated by the binary code of computer science. It is not structured through prostheses that can lead back to some form of materiality, but it is defined and specified with prostheses and connective intelligences which involves a relational, communicative, experiential sharing process for the creation of artistic practice communities.